2018
DOI: 10.1177/1464884918762362
|View full text |Cite
|
Sign up to set email alerts
|

Taming the ‘trolls’: How journalists negotiate the boundaries of journalism and online comments

Abstract: The relationship between online commenters and journalists has been challenged as frustrated journalists pull back on commenting and introduce rules to make it more difficult to participate. As new rules and policies emerge, journalists engage in a public campaign to change how commenting and journalism are perceived. This study seeks to understand how journalists attempt to frame commenting and its role alongside journalism. Boundary work was used to consider how journalists use public statements about commen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…There were 517 comments at the time I undertook this research in 2018 and most had been posted in the days and weeks following the review's publication. Below the line means comments posted below online articles by individuals expressing opinions, arguing and performing identities (Wolfgang 2018). These comments are made by people who choose to add to the debate.…”
Section: Methodsmentioning
confidence: 99%
“…There were 517 comments at the time I undertook this research in 2018 and most had been posted in the days and weeks following the review's publication. Below the line means comments posted below online articles by individuals expressing opinions, arguing and performing identities (Wolfgang 2018). These comments are made by people who choose to add to the debate.…”
Section: Methodsmentioning
confidence: 99%
“…Contemporary research has also shown an uneasiness with an uncritical valorising of close journalistaudience interactions due to the rise of abusive online users. Individual journalists have been responsible for expelling menacing online users and maintaining protected online sites (Binns 2012;Lewis, Zamith & Coddington 2020;Wolfgang 2018). Increasingly, social media have become sites of struggle for journalistic authority in online spaces too often full of trolls (Molyneux and Mourão 2019;Robinson 2010).…”
Section: Journalists' Online Interactionsmentioning
confidence: 99%
“…Added to this situation are criticisms of poor quality regarding the contributions (Reich, 2011;Robinson, 2010), or the so-called "dark participation." This is a reference to detrimental types of involvement (Quandt, 2018, p. 37), in the form of disinformation campaigns (Frischlich, Boberg & Quandt, 2018), trolling and cyberbullying, which require the implementation of moderating actions (Wolfgang, 2018).…”
Section: The Evolution Of the Digital Narrative: Between Utopia And Realitymentioning
confidence: 99%